An External Ophthalmomyasis Case Presented with Orbital Cellulitis Symptoms - Canleblebici, Mehmet; Koylu, Sara; Çatak, Onur (My University, 2023)
Oestrus ovis larvae are the most common cause of ophthalmomyiasis. It is frequently observed in the spring and summer in agri- cultural areas where there are many livestock animals, and these larvae generally cause external ophthalmomyiasis. Here, we report an atypical case with orbital cellulitis symptoms due to external ophthalmomyiasis. A 51-year-old male patient was referred to the outpatient clinic with the right eye erythema and swelling of the periorbital tissues, conjunctival congestion, chemosis, mucopurulent discharge, and eye movement limi- tation who diagnosed as orbital cellulitis with magnetic resonance imaging-based. During the careful ophthalmological examination, the mobile larvae were removed from the conjunctiva and slit-lamp examination revealed that the patient has infected with the first stage ovis larvae. He was treated with antibiotics and antihistamines as oral therapy and topically with antibiotics, steroids, and anticholinergics and recovered without complications. External ophthalmomyiasis may cause orbital cellulite findings with allergic reaction without internal ophthalmomyiasis and con- fuse the diagnosis.
Keywords: External ophthalmomyiasis; oestrus ovis; orbital cellulitis; orbita; eye lid